Student–Teacher Relationship: Its Measurement and Effect on Students’ Trait, Performance, and Wellbeing in Private College - Bai, Li ying; Li, Zi ying; Wu, Wen xin; Liu, Li yue; Chen, Shao ping; Zhang, Jing; Zhu, Julie N. Y. (Frontiers in Psychology, 2022)
Student–teacher relationships (STRs) have been examined by many studies. However, an omission still exists, the existing scales are not appropriate for studying STRs in private colleges because of the special character of these schools. This paper presents the development and validation of Private-College Student–Teacher Relationship Scale (PCSTRS), the first instrument to evaluate student–teacher relationships (STRs) in private colleges. The PCSTRS has six dimensions: trust, interaction, intimacy, care, approval, and comfort. In our main study, the validity and reliability of the six-factor PCSTRS model were demonstrated. The result of internal consistency coefficient indicated the high reliability of the scale, and the result of concurrent validity indicated the significant correlational relationships between the PCSTRS with other STR measures. In supplementary study, the PCSTRS was administered to 360 participants to confirm the applicability of PCSTRS and investigate the relation of STRs and students' traits, performance, and well-being, as well as the differences between the private school and the public school in this relation; the analyses revealed that there were significant differences in trust, intimacy and care between private and public colleges; positive correlations were found between STRs and self-esteem, self-efficacy, academic performance, extracurricular activity involvement, and subjective well-being. Present research-firstly develops the PCSTRS, examined the reliability and validity, and provides the proposed nomological network among related constructs.